Production and Preliminary Characterization of Alkaline Protease from Aspergillus flavus and Aspergillus terreus - P. Chellapandi (E-Journal of Chemistry, 2010)
Proteases are being an industrial candidate, which are widely used in food, bakery, and beverage and detergent industry. In leather industry, alkaline proteases are exhibiting a prominent role in unhairing and bating processes. An extensive use of filamentous fungi, especially Aspergillus species has been studied elaborately. Although, the significant application of alkaline protease produced from these strains in leather industry is being limited. Aspergillus flavus and Aspergillus terreus found as the potential strains for production of tannery protease in submerged fermentation. To improve the productivity of this enzyme in liquid broth, various media ingredients have been optimized. The crude and partially purified proteases preliminarily characterized and used for unhairing processes at lab scale in tannery. The protease obtained from these strains showed the good activity in wide alkaline condition at 50 °C suggesting the possibility of using in leather and detergent industry.